International network for evaluating outcomes of neonates: outputs and future directions - Shah P.S.; Isayama T.; Helenius K.K.; Feliciano L.S.; Beltempo M.; Bassler D.; Håkansson S.; Rusconi F.; Modi N.; Battin M.; Vento M.; Adams M.; et al. (AME Publishing Company, 2025)
Ten neonatal networks from 11 countries—Australia, New Zealand, Canada, Finland, Israel, Japan, Spain, Sweden, Switzerland, the Tuscany region of Italy, and the UK—came together in 2012 to form the International Network for Evaluating Outcomes of Neonates (iNeo): an international collaboration of population-representative, national neonatal datasets. The result has been a powerful platform for epidemiological, outcomes-based, and applied health services and policy research. The network has successfully collaborated to evaluate variations in health service organization, practices, and outcomes, with an aim to harmonize processes and identify areas for quality improvement in the various countries. We have identified marked variations in outcomes such as mortality, severe neurological injury, and treated retinopathy of prematurity; and highlighted the important need for the neonatal community to harmonize criteria for diagnosing bronchopulmonary dysplasia. Despite marked changes in the respiratory management of extremely preterm neonates with the aim to avoid mechanical ventilation, judicious use of oxygen, and less invasive administration of surfactant, rates of bronchopulmonary dysplasia have continued to rise in most countries. This may be due to marked discrepancies in the diagnostic criteria for bronchopulmonary dysplasia in extremely preterm neonates. We were able to conduct a detailed survey of more than 300 neonatal units worldwide and link the responses with actual patient data to generate hypotheses to evaluate in future studies. Specific areas of investigation have included preventing necrotizing enterocolitis, managing patent ductus arteriosus, and managing neonates with critical events such as severe intraventricular hemorrhage. In addition, we studied the physical design of neonatal units from family-centered care delivery point of view and multidisciplinary team inclusion in care of neonates. In this review, we summarize our opportunities for improvement and future plans for the collaboration. We also highlight the challenges we face as an international collaboration, such as sustainability and funding.